Ekonomi Kreatif: Menginovasi Hasil Pertanian untuk Meningkatkan Pendapatan Desa Sumber Urip Kecamatan Selupu Rejang - Tika Oktarina; Puspa Rini; Anadiya Pingki; Sucipto Febrianto; Harifin Saputra (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
This community service program focuses on the theme of creative economy with the aim of encouraging innovation in agricultural products to increase added value and income for Micro, Small, and Medium Enterprises (MSMEs) in Sumber Urip Village, Selupu Rejang District, Rejang Lebong Regency. Although the village has abundant agricultural potential, local products have not been optimally developed due to limited knowledge in processing, packaging, and marketing. The program employed a participatory-educative approach that emphasized active community involvement at every stage, including potential identification, socialization of creative economy concepts, product innovation training, and practical assistance in packaging and marketing. The participants consisted of farmers, MSME actors, and the Bukit Kaba Tourism Awareness Group (Pokdarwis) as strategic partners in developing a tourism-based market. The results indicate that the implementation of creative economy principles improved community understanding of product innovation, hygienic and value-added packaging, and appropriate marketing strategies targeting Bukit Kaba visitors. The strategic selling location at the Bukit Kaba tourism post further enhanced product visibility and market reach. Overall, this program demonstrates that creative economy-based community assistance can effectively strengthen MSME competitiveness, increase household income, and promote sustainable integration between agriculture, local entrepreneurship, and rural tourism development.